A fluorescent probe for the dual detection of mercury ions and thiols based on a simple coumarin derivative. (16th November 2019) - Tao, Pei; Chen, Dongling; Xu, Zhenxiang; Song, Yanxi; Li, Hongqi; Xian, Chunying
Abstract: A fluorescent probe based on a simple coumarin derivative could recognise mercury ions (Hg(ii )) and thiols selectively in aqueous solution. The addition of Hg(ii ) induced a blue shift of the fluorescence emission band of the probe while the fluorescence was almost quenched by the addition of p‐toluenethiol or cysteine (Cys). The detection limit of the probe towards Hg(ii ) and Cys was 8 µmol/L. The probe could be used for the detection of Hg(ii ) and thiols by the naked eye under ultraviolet light irradiation.